Experimental investigations to establish correlation between Stribeck curve, specific film thickness and statistical parameters of vibration and sound signals in a spur gear system. (April 2016) - Lee, Sang-Kwon; Amarnath, M
The use of a gear as a power transmitting machine element in engineering applications is quite extensive. Under service conditions gear teeth contacts have a tendency for deterioration due to contact fatigue, wear, material defects, lubrication failure etc. Gear teeth surface deterioration triggers several types of failures such as abrasive wear, scuffing, micro pitting and spalling. The abovementioned faults influence the changes in the vibration and sound signals in the gear system. This paper presents the novel results of experimental investigations carried out to assess the surface fatigue wear in a spur gear system. Estimation of specific film thickness, measurement of reduction in tooth thickness, visual examination of wear mechanisms on the gear teeth and their effects on the statistical parameters of vibration and sound signals are considered in this study. In order to confirm the hypothesis of dependency of surface fatigue wear, specific film thickness and sound and vibration signals the results of statistical parameters obtained from sound and vibration signals have been correlated with the Stribeck curve.